The Role of Live Streaming Value Perception Factors in Forming Trust and Repurchase Intention - Rahmita, Tyas Ayu; Albari, Albari (Jurnal Aplikasi Manajemen, 2025)
The rapid growth of e-commerce has led to the increasing popularity of live streaming as a digital marketing strategy, allowing real-time interaction between sellers and consumers. Despite its rising adoption, there is still a need to understand how live streaming influences customer trust and repurchase intention, particularly in the context of the ShopeeLive platform. This study aims to determine the effect of live streaming on building customer trust and repurchase intention on the ShopeeLive Platform. Through the Stimulus-Organism-Response (SOR) approach, this study examines the influence of utilitarian, hedonic, and symbolic values that customers perceive during live streaming on trust in sellers and products, and their impact on repurchase intention. This study uses a quantitative approach. The number of respondents sampled in this study was 350 people who filled out questionnaires using Google Forms with convenience sampling techniques. The analysis technique used was Structural Equation Modeling (SEM) using the AMOS version 24.0 program. The results showed ten supported and two unsupported hypotheses, which showed that utilitarian and symbolic value positively and significantly affected trust in the product, the seller, and repurchase intention. The hedonic value variable has a positive and significant effect on trust in the seller, but has no significant effect on trust in the product or repurchase intention. The novelty of this study is replacing the variable with repurchase intention and expanding the utilitarian value measurement, including an added indicator on the perception of ShopeeLive’s more attractive and consistent price deals. These findings provide important implications for e-commerce businesses paying more attention to utilitarian and symbolic aspects in live streaming, which are proven to be more effective in building trust and repurchase intention.